THE IMPACT OF MOBILE-ASSISTED LANGUAGE LEARNING ON VOCABULARY RETENTION AMONG ESL STUDENTS - Ibrohimova Nozima (TADQIQOTLAR, 2025)
Abstract: This article explores the effects of mobile-assisted language learning (MALL) on vocabulary retention among learners of English as a Second Language (ESL). As mobile technology becomes increasingly embedded in daily life, its role in language learning environments is growing. The paper examines how mobile applications and tools influence vocabulary acquisition and long-term retention, highlighting both the benefits and challenges of their integration into ESL education. Practical recommendations for educators and suggestions for future research are also discussed.